High connectivity and directional gene flow in European Atlantic and Mediterranean populations of Ciona intestinalis sp. A. (28th November 2014) - Affinito, Ornella; Andreakis, Nikos; Caputi, Luigi; Marino, Rita; Pannone, Raimondo; Sordino, Paolo; Procaccini, Gabriele
Abstract: Understanding the factors that cause population divergence has long been of interest to marine biologists in their attempts to interpret the effect of human‐mediated vectors. Broadcast‐spawning species with limited dispersal capability are excellent candidates to measure the present‐day patterns of genetic diversity. The tunicate Ciona intestinalis (Ascidiacea) is comprised of a complex of morphologically cryptic species that form vigorous aggregates in eutrophic habitats (harbors, gulfs and lagoons) where they can compete with the epibenthic community and cause biofouling problems. This study investigated biogeographic variability and migration patterns of C. intestinalis sp. A along Northeast Atlantic and Mediterranean coasts using microsatellite markers. Data presented here on 371 specimens collected from 17 populations reveal high genetic polymorphism, but with a deficit of heterozygote deficiency. Absence of evidence for isolation by distance suggests that the genetic patterns do not reflect the geographic distribution of sampled populations. Substantial gene flow and artificial potential for dispersal boost high levels of within‐population genetic variability and prevent genetic differentiation within and between seas. A predominant eastward migration pattern was revealed by the data set, with very limited opportunity for C. intestinalis sp. A to travel westward. This directional movement indicates that other properties ( e.g . habitat quality, genetic traits, mating system, life cycle) may cause adaptive divergence at a large biogeographic scale.